2001
DOI: 10.1105/tpc.13.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Distinct Specificity Determinants in Resistance Protein Cf-4 Allows Construction of a Cf-9 Mutant That Confers Recognition of Avirulence Protein AVR4

Abstract: The tomato resistance genes Cf-4 and Cf-9 confer specific, hypersensitive response-associated recognition of Cladosporium carrying the avirulence genes Avr4 and Avr9 , respectively. Cf-4 and Cf-9 encode type I transmembrane proteins with extracellular leucine-rich repeats (LRRs). Compared with Cf-9, Cf-4 lacks two LRRs and differs in 78 amino acid residues. To investigate the relevance of these differences for specificity, we exchanged domains between Cf-4 and Cf-9, and mutant constructs were tested for mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
88
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 41 publications
7
88
0
Order By: Relevance
“…However, we observed that overexpression of the LRR domain of AtLRX1, despite its ability to sequester the ligand of the native AtLRX1 protein and induce a dominant negative effect in root hairs, had no influence in the rest of the plant where other LRXs are active (Baumberger et al, 2001). This result indicates that the flanking regions of the LRRs might contribute to the specificity of the interaction with the ligand as observed for the LRRs of the tomato and flax (Linum usitatissimum) resistance genes Cf-4, L6, and L7 (Ellis et al, 1999;Van der Hoorn et al, 2001). The existence of family-or paralog/ortholog-specific regions adjacent to the conserved region of the N-termini of the LRX proteins supports this notion.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, we observed that overexpression of the LRR domain of AtLRX1, despite its ability to sequester the ligand of the native AtLRX1 protein and induce a dominant negative effect in root hairs, had no influence in the rest of the plant where other LRXs are active (Baumberger et al, 2001). This result indicates that the flanking regions of the LRRs might contribute to the specificity of the interaction with the ligand as observed for the LRRs of the tomato and flax (Linum usitatissimum) resistance genes Cf-4, L6, and L7 (Ellis et al, 1999;Van der Hoorn et al, 2001). The existence of family-or paralog/ortholog-specific regions adjacent to the conserved region of the N-termini of the LRX proteins supports this notion.…”
supporting
confidence: 69%
“…In each LRR, a region of the consensus sequence (xxLxLxx) is predicted to form a ␤-strand/ ␤-turn structure in which the variable residues (x) are exposed to the solvent and determine the specificity of the interaction. This region of the LRR is subjected to diversifying selection in plant resistance genes (McDowell et al, 1998;Meyers et al, 1998;Ellis et al, 1999;Van der Hoorn et al, 2001). The observation that among different LRXs, the solvent-exposed amino acids are well conserved or even identical (AtLRX3/4 and AtLRX6/7) suggests that the LRX proteins interact with very similar or identical ligands.…”
mentioning
confidence: 99%
“…In previous functional studies, the C1 region has been implicated in providing the recognition specificity of RLPs. Deletion of LRRs and introduction of point mutations in the C1 region of Cf-9 changes the specificity of Cf-9 to that of Cf-4 ( Van der Hoorn et al, 2001;Wulff et al, 2001). Our analyses reveal the C1 region to be highly variable, particularly in the number of LRRs.…”
Section: Discussionmentioning
confidence: 80%
“…This domain in BRI1 has now been shown to be involved in direct binding to brassinolide (Kinoshita et al, 2005). On the other hand, the C2 domains of Cf-9 and Cf-4 are identical, and determinants of the distinct recognition achieved by these proteins reside in LRRs 10 to 16 of domain C1 ( Van der Hoorn et al, 2001;Wulff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation